Positive Intelligence and Critical Thinking in Students of a Private University in San Martín, Perú - Mabel, Contreras-Julián Rosa; Manuel, Delgado-Bardales José; Keller, Sánchez-Dávila; Pilar, Palomino-Alvarado Gabriela del (Journal of Ecohumanism, 2024)
Organizations focus on the results of their workers, measuring productivity and efficiency, but they do not ensure personal and professional growth. Furthermore, there are no scientific studies that suggest strategies for working as a team to achieve not only institutional purposes, but also happiness and success. Furthermore, the research that has been carried out on intelligence has only focused on aspects: emotional, cognitive, social, financial, spiritual, multiple intelligences, among others, but has not focused on positive intelligence. So far there is only one study on positive intelligence by Chamine, in 2013, but they still do not give it importance. This has led to carrying out this scientific research in order to manage and control thought. Therefore, the objective was to establish the relationship between positive intelligence and critical thinking in university students. The basic type, with a quantitative approach, non-experimental design with a correlational descriptive level. The population and sample were made up of 80 Master's students in Educational Psychology. As results, it was obtained that most of the dimensions of positive intelligence are at the medium level, such as Controller, hyper-achiever, hyper-rational, hyper-vigilant, accommodating, restless, rigorous, victim and judge. Regarding the dimensions of critical thinking, most are at a medium level such as certainty, logic, justice, importance and depth. It was concluded that there is a very low, but non-significant positive relationship between positive intelligence and critical thinking with a Spearman's Rho statistical coefficient of 0.151 with a p-value of 0.181.